1987
DOI: 10.4141/cjps87-079
|View full text |Cite
|
Sign up to set email alerts
|

INHERITANCE OF GOITRIN, VOLATILE ISOTHIOCYANATES AND THIOCYANATE ION IN CABBAGE (Brassica oleracea L. ssp. capitata L.)

Abstract: selon laquelle les gdnes qui r6gissent I'h6r6dit6 de la goitrine et des isothiocyanates volatiles seraient li6s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These findings are similar to those of Chong et al (1985) for cabbage population; however, there were more goi trin-free individuals in the broccoli than in the cabbage population. Chiang et al (1987) reported that the in heritance of goitrin in cabbage is compli cated by a maternal effect. This is most likely true also for broccoli, since the plant lines used in this study (Tables 1, 2) are related to the cabbage selections previously studied (Chiang et al, 1987) and both belong to the c genome.…”
Section: Thiocyanatementioning
confidence: 99%
See 3 more Smart Citations
“…These findings are similar to those of Chong et al (1985) for cabbage population; however, there were more goi trin-free individuals in the broccoli than in the cabbage population. Chiang et al (1987) reported that the in heritance of goitrin in cabbage is compli cated by a maternal effect. This is most likely true also for broccoli, since the plant lines used in this study (Tables 1, 2) are related to the cabbage selections previously studied (Chiang et al, 1987) and both belong to the c genome.…”
Section: Thiocyanatementioning
confidence: 99%
“…Chiang et al (1987) reported that the in heritance of goitrin in cabbage is compli cated by a maternal effect. This is most likely true also for broccoli, since the plant lines used in this study (Tables 1, 2) are related to the cabbage selections previously studied (Chiang et al, 1987) and both belong to the c genome. Thus, in breeding programs that aim to reduce goitrin, it would be wise to use plants with no or low goitrin contents as the female parents.…”
Section: Thiocyanatementioning
confidence: 99%
See 2 more Smart Citations